Leading bank credit portfolio strategies - Dvorak, Brian (Henry Stewart Talks, 2007)
Leading banks manage their credit portfolios actively, Active credit portfolio management objectives and principles, Active credit portfolio management trends and success stories, Leading bank economic capital management strategies, Uses of required economic capital at leading banks, Leading bank credit portfolio management organizational models, Leading bank credit portfolio management strategies, Adopting leading bank strategies
Archived at 2022/04/04